Percutaneous core biopsy of small renal mass lesions: a diagnostic tool to better stratify patients for surgical intervention. (13th July 2012) - Menogue, Stuart R.; O'Brien, Beverley A.; Brown, Alexandra L.; Cohen, Ronald J.
Abstract : Study Type – Prognosis (case series) Level of Evidence 4 What's known on the subject? and What does the study add? Biopsy of incidentally detected small renal masses is a safe and accurate method of determining benign from malignant lesions. Renal biopsy identifies over one quarter of cases as benign; however, one in five biopsy procedures results in insufficient material for a diagnosis. The study contributes an additional 268 renal biopsy cases to the literature and further assesses the accuracy of biopsy and its ability to reduce the number of patients undergoing radical surgery for benign lesions. The results of lesions managed conservatively with follow‐up are also presented. Furthermore, the study identifies an improved diagnostic trend for needle core biopsies over the period. OBJECTIVES: To further validate the safety and diagnostic accuracy of percutaneous core biopsy in small renal masses ([SRMs]≤4 cm) in response to the rising prevalence of renal 'incidentalomas'. To determine the value of percutaneous core biopsy in its ability to influence the choice of intervention or surveillance for the management of SRMs. PATIENTS AND METHODS: We collected data on the incidence of benign, malignant and non‐diagnostic samples from 268 SRM (clinical T1a) biopsies performed at our institution between 1998 and 2009. The diagnostic accuracy of biopsy in small renal lesions was examined in cases proceeding to nephrectomy. Follow‐up on the remaining non‐surgical cases was performed. RESULTS: SRMs (≤4 cm, clinical T1a) constituted 59% of all renal lesions diagnosed; 80% of these biopsies were diagnostic and 20% were non‐diagnostic. Of the diagnostic samples, 74% were malignant and 26% were benign. Thirty‐three percent (17 of the initial 52) non‐diagnostic samples underwent re‐biopsy, with 94% yielding a histological diagnosis on repeat sampling. Fifty‐eight percent of our diagnostic masses underwent nephrectomy, returning a renal biopsy accuracy rate of 100% for identifying lesions as benign or malignant. Of the 98 observed masses, 49% were benign, 28% malignant and 23% were non‐diagnostic. In 63% of these cases, size remained stable in the follow‐up period. CONCLUSIONS: Percutaneous core biopsy continues to provide an accurate and safe tool for preoperative tissue diagnosis of SRMs and should be offered to patients before considering surgical intervention. With regard to both benign and malignant T1a renal lesions, in select patient groups, those electing to undergo observation may expect favourable short‐ to medium‐term outcomes.